The modelling of internal combustion engine thermal systems and behaviour - Morgan, Tessa Joanne (2003)
The work described in this thesis concerns the continued development and application of a computational model to simulate the thermal behaviour of internal combustion engines. The model provides information on temperature and heat flow distributions within the engine structure, and on temperatures of oil, coolant and engine-out exhaust gas. Sub-models calculate friction levels, fuel flow rates and gas-side heat transfer, including the effects of exhaust gas recirculation (EGR), spark advance and turbocharging. The effects of auxiliary components such as a cabin heater, oil cooler, intercooler, supplementary heater and EGR cooler can also be simulated.